Children and Youth Spiritual Songs and Hymns of Western Europe Mennonites: History and Modernity - Brezhnieva, Svitlana (Pedagogical Discourse, 2017)
The history of child’s and youth spiritual songs and hymns development, analysis of hymns’ texts, that represent transmission of appearance and the large spiritual feelings of child gradual increase, research of authors of these hymns in relation to intention of creation of these songs, is considered in the article, influence of every word on child consciousness, that enriches their inner world in the process of theoretical analysis among evangelic lean singing it is distinguished: 1) cycle of hymns for children and youths that contain the elements of worship; 2) songs of communion; 3) lean confessions; 4) evangelic songs-declamations. The research conclusion is definition about importance of bringing to children spiritual hymns implementation of appealing to their emotionality, sensitiveness, necessity in execution the general operating under family and education of cognation with a confessional association in the process of spiritual increase. The implementation of hymns clarifies consciousness of child, develops it vocal capabilities, emotional mobility, singing of religious hymns forms sense of belonging to the confessional association, induces a child to mastering of spiritual treasures. To perspective directions of research is taken positions are in relation to comparison of musical and literary texts maintenance, study of emotionally-vivid relation of children to religious hymns’ musical essence, illumination of musical symbolics oof spiritual hymns’ semantic filling. In the article the self attaching of child is marked on importance to implementation of spiritual hymns exactly in a domestic circle, as it assists activation of necessity to spiritual life. Key words: family, child, musical education, spirituality, spiritual songs, hymns, hymnsgraphy, mennonites, scripture, songsinging, confessions, psalms.